Flexibility estimation of electric vehicles and its impact on the future power grid - Jiexiang Wu; Li Li; Jiangfeng Zhang; Boyi Xiao (International Journal of Electrical Power & Energy Systems)
Electric vehicles offer environmental benefits but pose challenges to power grids during peak demand. This study introduces a method to optimize electric vehicle charging and incorporate vehicle-to-grid technology, aiming to minimize electricity costs and electric vehicle loads during peak periods. Two models are developed to evaluate electric vehicle owners’ willingness to participate in both non-vehicle-to-grid and vehicle-to-grid scenarios, providing insights into future peak demand increases and potential reductions through optimization.A case study in Texas, USA, utilizing data from the Pecan Street database, reveals that by 2030, the increase in peak electric vehicle charging demand could exceed the current levels by over 4.7 times. This surge is up to 3.16% of the total electricity demand in Texas. However, with the implementation of the proposed optimization methods, electric vehicles could potentially feed about 747 MWh of energy back into the grid, effectively transforming them from energy consumers to suppliers during high-demand periods. This demonstrates the crucial role that electric vehicles, coupled with strategic charging and vehicle-to-grid technologies, can play in not only mitigating emissions but also in enhancing grid stability and efficiency.